2014
DOI: 10.1039/c3mt00132f
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein polymorphisms in pathological processes

Abstract: Metallothioneins (MTs) are a class of metal-binding proteins characterized by a high cysteine content and low molecular weight. MTs play an important role in metal metabolism and protect cells against the toxic effects of radiation, alkylating agents and oxygen free radicals. The evidence that individual genetic characteristics of MTs play an important role in physiological and pathological processes associated with antioxidant defense and detoxification inspired targeted studies of genetic polymorphisms in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 112 publications
3
79
0
Order By: Relevance
“…These results suggest that the contribution of MT to longevity is relatively high in prolongevity genes. Several polymorphisms have been detected in human MT genes and these are associated with pathological processes including aging, cancers, diabetes, and inflammation (Raudenska et al, 2014). Therefore, the decreased synthesis and defective function of MT proteins may be potential therapeutic targets of aging or life shortening in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the contribution of MT to longevity is relatively high in prolongevity genes. Several polymorphisms have been detected in human MT genes and these are associated with pathological processes including aging, cancers, diabetes, and inflammation (Raudenska et al, 2014). Therefore, the decreased synthesis and defective function of MT proteins may be potential therapeutic targets of aging or life shortening in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the tissue distribution can be well detected by immunohistochemistry, which was based for performing meta-analysis of metallothionein as an immunohistochemical marker of cancer [36]. Based on the published data it can be concluded that MT could be considered as a marker of tumour diseases, however, combination of mRNA and protein levels is needed [37,38]. Therefore, we aimed our attention at summarization of MT mRNA determination.…”
Section: Metallothionein Expressionmentioning
confidence: 99%
“…As mentioned previously, MTs are expressed by four different genes (MT1 , MT2 , MT3 , and MT4) with several isoforms [28,29]. Earlier data suggested that only two genes, namely MT1 and MT2 , are expressed in the presence of Pb; differences in MT3 expression were not associated with exposure to the metal, while, so far, the role of the MT4 gene is still not well understood [30,31].…”
Section: Resultsmentioning
confidence: 99%